2020
DOI: 10.21203/rs.3.rs-73166/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beneficial effect of indigo naturalis on acute lung injury induced by influenza A virus

Abstract: Background: Infections induced by influenza viruses, as well as coronavirus disease 19 (COVID-19) pandemic induced by severe acute respiratory coronavirus 2 (SARS-CoV-2) led to acute lung injury (ALI) and multi organ failure, during which traditional Chinese medicine (TCM) played an important role in treatment of the pandemic. The study aimed to investigate the effect of indigo naturalis on ALI induced by influenza A virus (IAV) in mice.Method: The anti-influenza and anti-inflammatory properties of aqueous ext… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
1
1
0
Order By: Relevance
“…In addition, PFWE decreased the gene expression and protein production of in ammatory cytokine (IL-6) and chemokine (CCL2/ MCP-1). Although this is the rst study to show the e cacy of PFWE in controlling ARDS, similar results have been reported by applying other TCM, such as Indigo naturalis, Huang Qin, or Sophorae avescentis Radix [21][22][23]. Our data further support the use of TCM for the treatment of pulmonary diseases in the acute phase.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, PFWE decreased the gene expression and protein production of in ammatory cytokine (IL-6) and chemokine (CCL2/ MCP-1). Although this is the rst study to show the e cacy of PFWE in controlling ARDS, similar results have been reported by applying other TCM, such as Indigo naturalis, Huang Qin, or Sophorae avescentis Radix [21][22][23]. Our data further support the use of TCM for the treatment of pulmonary diseases in the acute phase.…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, oral drug administration exacerbates the metabolic burden in the liver, which might result in metabolic disturbances and thereby increasing the susceptibility to carcinogenesis [86]. Issues regarding hepatotoxicity have been resolved by the promoted liver regeneration by BT [87], PP [88], BD [89], CH [90,91], LC [92,93], SK [94], and CWT [95]. ③ IBD patients are susceptible to malnutrition including anemia, amino acid, and vitamin deficiency [96], which could be rescued by PP [97] due to its hematopoiesis-promoting effect [98][99][100] and by the addition of pearl that is produced from shellfish mollusks which contain 20 amino acids and Fe and Mg elements [101].…”
Section: Discussionmentioning
confidence: 99%